AB1237 Patients' perspectives and experience of psoriasis and psoriatic arthritis: a systematic review and thematic synthesis of qualitative studies. (12th June 2018) - Sumpton, D.J.; Kelly, A.; Tunnicliffe, D.J.; Craig, J.C.; Hassett, G.; Chessman, D.; Tong, A.
Abstract : Background: Patients with psoriasis and psoriatic arthritis have a lower health related quality of life than the normal population and experience high rates of treatment dissatisfaction 1 . The complexity of unmet needs in diagnosis and treatment 2 necessitate a deep understanding of the experience of people with both conditions to guide development of outcomes important to patients and improve patient centred care. Objectives: To describe the perspectives and experiences of patients with psoriasis and psoriatic arthritis. Methods: Databases (MEDLINE, Embase, PsycINFO, CINAHL) were searched to October 2016. Thematic synthesis was used to analyse the findings. Results: From 46 studies (n=37 psoriasis and n=9 psoriatic arthritis) involving 1290 adult patients with psoriasis (n=1105) and psoriatic arthritis (n=185) we identified six themes (with subthemes): suffering uncontrollable and ongoing upheaval (dictating life choices and course, disrupting role functioning, limited by debilitating symptoms, unstoppable and far reaching fatigue); weighed down by mental load (struggling with unrecognised distress, anxiety provoked by the volatility and constancy of symptoms, depleting motivation and pleasure); harbouring shame and judgement (marked as unhygienic and contagious, rejected and isolated, resenting own appearance, pain and embarrassment in intimacy); demoralised by inadequacies and burden of therapy (disappointed by unmet expectations of treatment benefit, daily drudgery, deterred by unpalatable or inconvenient treatments, disempowered by lack of personalised care, fearing long term side effects); gaining control (making sense of the condition, shutting the disease out, accepting a new health status, attuning to the body); and making confident treatment decisions (trading off perceptible benefits against safety and convenience, relying on family input, reassured by clinician acknowledgement of fears, seeking empowering relationships with clinicians). Conclusions: Patients with psoriasis and psoriatic arthritis contend with profound disruption in their functioning, roles and life course; fear deterioration of their health; and have unmet expectations about their treatment and care. Patients with psoriasis feel marked by their disease, stigmatised and rejected by others while patients with psoriatic arthritis experience social withdrawal and depleted motivation due to fatigue, joint impairment and pain. Establishing therapeutic relationships, addressing treatment expectations, and supporting psychosocial needs may help to improve satisfaction and outcomes in patients with psoriasis and psoriatic arthritis. References: [1] Katherine M. Mercy, Kenneth B. Gordon, Amy S. Paller. Patient Satisfaction and Quality of Life in Psoriasis and Psoriatic Arthritis. JAMA. 2014;312(24):2676–2677 [2] Helliwell, et al. Qualifying Unmet Needs and Improving Standards of Care in Psoriatic Arthritis. Arthritis Care & Research Vol. 66, No. 12, December 2014, pp 1759–1766 Disclosure of Interest: None declared